2019
DOI: 10.1051/0004-6361/201935534
|View full text |Cite
|
Sign up to set email alerts
|

The CARMENES search for exoplanets around M dwarfs

Abstract: Although M dwarfs are known for high levels of stellar activity, they are ideal targets for the search of low-mass exoplanets with the radial velocity (RV) method. We report the discovery of a planetary-mass companion around LSPM J2116+0234 (M3.0 V) and confirm the existence of a planet orbiting GJ 686 (BD+18 3421; M1.0 V). The discovery of the planet around LSPM J2116+0234 is based on CARMENES RV observations in the visual and near-infrared channels. We confirm the planet orbiting around GJ 686 by analyzing t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 88 publications
(74 reference statements)
3
13
0
Order By: Relevance
“…Full set of Bayes Factor Periodograms for GL 686. The red line denotes the 15d planet signal originally identified in Affer et al (2019) and Lalitha et al (2019) and confirmed again in this work. The gold lines show the ∼40 day and ∼2,000 day signals that we identify as the star's rotational and magnetic activity cycles, respectively.…”
Section: ©2020supporting
confidence: 85%
See 2 more Smart Citations
“…Full set of Bayes Factor Periodograms for GL 686. The red line denotes the 15d planet signal originally identified in Affer et al (2019) and Lalitha et al (2019) and confirmed again in this work. The gold lines show the ∼40 day and ∼2,000 day signals that we identify as the star's rotational and magnetic activity cycles, respectively.…”
Section: ©2020supporting
confidence: 85%
“…We also confirmed the orbital parameters of two previously published low-mass planets. First, we derived an updated orbital solution for the planet orbiting the M1.0V star GJ 686 reported by Affer et al (2019) and Lalitha et al (2019) using an additional 134 new RV APF measurements and 18 new PFS measurements. And second we updated the orbital solution of the planet orbiting the M3.0V star HD 180617 detailed in Kaminski et al (2018), adding 126 new APF measurements to the combined data set.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…distinguish between planetary and activity-related signals in RV time series. These projects include both M-dwarf data taken under the CARMENES survey program (Kaminski et al 2018;Luque et al 2018;Reiners et al 2018b;Lalitha et al 2019;Nagel et al 2019b;Perger et al 2019;Schöfer et al 2019) as well as open time observations of other cool stars (Luque et al 2019;Pallé et al 2019). We observe that the indicators in different stars display notable differences depending on the spectral type and activity level of the stars.…”
Section: Activity Analysismentioning
confidence: 69%
“…At a distance of 8.66 +0.13 −0.13 × 10 −2 au from the host star, GJ 3473 c receives 1.98 +0.17 −0.15 times the stellar flux compared to Earth, which places it outside the inner boundary of the optimistic habitable zone, 1.49 S ⊕ > S > 0.22 S ⊕ , as defined by Kopparapu et al (2014). The planet therefore is a temperate super-Earth or mini-Neptune such as GJ 887 c (Jeffers et al 2020), GJ 686 b (Lalitha et al 2019;Affer et al 2019), GJ 685 (Pinamonti et al 2019) or GJ 581 c (Udry et al 2007) (see Fig. 11).…”
Section: Gj 3473 Cmentioning
confidence: 99%